Should an Online Blogger Be Protected by the Illinois Reporter’s Privilege? - Donald L. Buresh (Journal of Advanced Forensic Sciences, 2020)
The question that this paper answer is whether the Illinois Reporter’s Privilege should protect an online blogger. The definitions of the terms “reporter,” “news medium,” and “source” quoted from 735 ILCS 5/8-902, followed by several examples. Second, a brief history of journalism is presented, where it is demonstrated that for hundreds of years, journalists and publishers alike engaged in their profession with little formal training, but rather with a sincere desire to convey the facts and the truth to their peers. Second, the essay outlines how Illinois and federal courts have employed the privilege in case law. In answering the question, the work examines whether WikiLeaks qualifies under the Illinois Reporter’s Privilege. The position taken is that the answer is yes. The idea is that if WikiLeaks qualifies under the privilege, then other online blogs also qualify. The opinion of the author is that the law is sufficient as it stands. There is no need to change its wording. Finally, some loose ends are discussed before reiterating the conclusion that the Illinois Reporters’ should not be changed.
Keywords: 735 ILCS 5/8-902